2013
DOI: 10.1007/s00404-013-2941-6
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of β-thalassemia in Guangxi Zhuang Autonomous Region, China

Abstract: Our prenatal diagnosis strategy proved to be highly effective in reducing severe thalassemia in pregnant populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Currently, the generally used effective method to prevent the birth of children with thalassemia is gene screening combined with prenatal diagnosis for pregnant-age couples. [16][17][18] According to the analysis in the peripheral blood samples from 31 512 couples/probands and 3828 prenatal samples, and retrospective analysis of genetic testing, our study found that the carrying rate of α-thalassemia was higher than that of β-thalassemia. For mutation types, α-thalassemia was mainly large deletion type, while β-thalassemia was mainly point mutation, which is consistent with Guangdong and Guangxi, the proportion of mutation types is also in line with the mutation frequency characteristics of the southern Chinese population.…”
Section: Discussionmentioning
confidence: 73%
“…Currently, the generally used effective method to prevent the birth of children with thalassemia is gene screening combined with prenatal diagnosis for pregnant-age couples. [16][17][18] According to the analysis in the peripheral blood samples from 31 512 couples/probands and 3828 prenatal samples, and retrospective analysis of genetic testing, our study found that the carrying rate of α-thalassemia was higher than that of β-thalassemia. For mutation types, α-thalassemia was mainly large deletion type, while β-thalassemia was mainly point mutation, which is consistent with Guangdong and Guangxi, the proportion of mutation types is also in line with the mutation frequency characteristics of the southern Chinese population.…”
Section: Discussionmentioning
confidence: 73%
“…Genomic DNA were extracted from peripheral blood leukocytes using DNA blood extraction kits (Tiangen Bio‐Tech Co. Ltd., Beijing, China). Molecular study for common alpha and beta defects in Chinese population were performed as previously described . Multiplex ligation‐dependent probe amplification (MLPA) was firstly used to analyze dosage changes of the β‐globin gene cluster for associated with (δβ) 0 ‐thal and HPFH mutations.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular study for common alpha and beta defects in Chinese population were performed as previously described. 13,14 Multiplex ligation-dependent probe amplification (MLPA) was firstly used to analyze dosage changes of the β-globin gene cluster for associated with (δβ) 0 -thal and HPFH mutations. Probes and reaction mixture for ligation and PCR were purchased from MRC-Holland (SALSA MLPA kit P102 HBB; MRC-Holland, Amsterdam, the Netherlands).…”
Section: Genetic Analysismentioning
confidence: 99%
“…In fact, the high prevalence of these conditions has led some governments to focus their resources on preconception testing and counseling for these heritable traits rather than on the less common and (generally) non-heritable aneuploidies. 128 , 129 Nevertheless, many countries in the Middle East, Africa, and South America still lack systematic and widespread prenatal screening programs. 130 …”
Section: Implementation In Lmicsmentioning
confidence: 99%